1989
DOI: 10.1128/aac.33.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the porins of Campylobacter jejuni and Campylobacter coli and implications for antibiotic susceptibility

Abstract: The major outer membrane protein was extracted from Campylobacter coli by Triton X-100/EDTA fractionation of cell envelopes. This heat-modifiable protein was shown to have pore-forming activity in black lipid bilayers. The C. coli porin formed a relatively small cation-selective pore with a mean single-channel conductance of 0.53 + 0.16 nS in 1.0 M KCI. There was no evidence of oligomer formation, which suggested that each protein monomer formed a pore. Pore-forming activity of the C. coli porin and similarly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…The predicted mature MOMP 33291 protein consisted of 403 amino acids with a calculated molecular mass of 43.5 kDa, comparable to the size (45 kDa) estimated by SDS-PAGE. MOMP 33291 contained a high portion of charged residues and is an overall negatively charged protein, compatible with the marked cationic selectivity of the pores formed by MOMP (10,33). cmp 33291 was found to be highly homologous (97% amino acid identity) to the recently released cmp sequences in strains NCTC 11168 (34) and 2483 (GenBank accession number U96452).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The predicted mature MOMP 33291 protein consisted of 403 amino acids with a calculated molecular mass of 43.5 kDa, comparable to the size (45 kDa) estimated by SDS-PAGE. MOMP 33291 contained a high portion of charged residues and is an overall negatively charged protein, compatible with the marked cationic selectivity of the pores formed by MOMP (10,33). cmp 33291 was found to be highly homologous (97% amino acid identity) to the recently released cmp sequences in strains NCTC 11168 (34) and 2483 (GenBank accession number U96452).…”
Section: Resultsmentioning
confidence: 97%
“…Since the cytotoxic preparation contained lipopolysaccharide, it was difficult to determine the actual component responsible for the observed cytotoxicity. MOMP was also speculated to be involved in the general resistance of C. jejuni to many hydrophilic antibiotics (33). These observations suggest that MOMP may have additional biological functions contributing to the adaptation of the pathogenic organism to various host environments.…”
mentioning
confidence: 85%
“…Attempts to purify the trimeric form of the HopE were unsuccessful because of its instability in SDS; however, the monomeric form was purified to homogeneity, and it formed functional channels in lipid bilayers. The instability in SDS of the HopE trimer is not an uncommon feature of porins trimers, since it is reported for a number of other bacterial species (18,20,29,37,38). Crosslinking experiments indicated that the HopE protein forms trimers in the outer membrane, indicating that HopE likely functions as a trimer in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Monomer porins and low-single-channel conductance are typical of porins isolated from bacterial species related to H. pylori, such as Campylobacter coli (0.53 nS) (18), Campylobacter jejuni (0.82 nS) (29), and Campylobacter rectus (0.49 and 0.60) (19). Nonetheless, it seemed possible that H. pylori possesses another class or species of porin(s) that might resemble the major porins of other gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacters possess a major porin, major outer membrane protein (MOMP), which appears to exist in a monomeric form as well as in a weakly associated trimeric form (650, 651) and likely yields OM permeability channels smaller than those of E. coli porins (652,653). The marked susceptibility of wild-type campylobacter strains to large, hydrophobic antibiotics such as macrolides may suggest the presence of an unusually permeable bilayer domain in the OM.…”
Section: Campylobacter Sppmentioning
confidence: 99%